SOLVABILITAS, RISIKO KREDIT DAN KINERJA KEUANGAN BANK PERKERDITAN RAKYAT (Jurnal Proaksi, 2022)
The ability of a bank to run its operations effectively is to determine its finances. This paper takes the topic of BUMD banking research, especially BPR in 2016-2020. The purpose of this study was to determine the effect of Non Performing Loans (NPL) and solvency on the financial performance of BPD in Indonesia. In this study, we used a population of BPRs registered with BUMD and used a sampling technique, namely purposive sampling with samples from BPR Yogyakarta and BPR BPR Magelang to analyze the data in this study, multiple linear regression was used to analyze the relationship between various factors and the desired outcome. Solvency is proxied by debt to asset ratio (DAR) and debt to equity ratio (DER), while credit risk is proxied by non-performing loan (NPL). For financial performance, Return on Assets (ROA) is a proxy for financial performance. The results of the analysis show that solvency is proxied by the ratio of debt to assets (DAR) and the ratio of debt to equity (DER) has an effect on financial performance and credit risk has an effect on financial performance.Keywords: Bank, DAR, DER, NPL, ROA